2022
DOI: 10.1007/s41871-022-00127-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward Single-Atomic-Layer Lithography on Highly Oriented Pyrolytic Graphite Surfaces Using AFM-Based Electrochemical Etching

Abstract: Atomic force microscopy (AFM)-based electrochemical etching of a highly oriented pyrolytic graphite (HOPG) surface is studied toward the single-atomic-layer lithography of intricate patterns. Electrochemical etching is performed in the water meniscus formed between the AFM tip apex and HOPG surface due to a capillary effect under controlled high relative humidity (~ 75%) at otherwise ambient conditions. The conditions to etch nano-holes, nano-lines, and other intricate patterns are investigated. The electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Apart from Si, materials such as, highly oriented pyrolytic graphite (HOPG), gold, silicon carbide and van der Waals materials such as transition metal dichalcogenides (TMD) are also potential candidates for atomic-scale manufacturing studies using AFM. As a step towards this, in our recently published article, we have shown that a single atomic layer removal over HOPG can be achieved [26].…”
Section: Introductionmentioning
confidence: 95%
“…Apart from Si, materials such as, highly oriented pyrolytic graphite (HOPG), gold, silicon carbide and van der Waals materials such as transition metal dichalcogenides (TMD) are also potential candidates for atomic-scale manufacturing studies using AFM. As a step towards this, in our recently published article, we have shown that a single atomic layer removal over HOPG can be achieved [26].…”
Section: Introductionmentioning
confidence: 95%
“…In addition, there are electrochemical modification [ 158 ], anodic oxidation [ 109 ], and ultraviolet photocatalysis modification [ 159 ] that can be considered for polishing. The search for more suitable modification approaches and finding a balance between modification and removal can focus research to improve the efficiency and precision of the chemical modification polishing processes.…”
Section: Chemical Modification Polishing Approachesmentioning
confidence: 99%
“…Hence, by reducing the tool size, the electrochemical reaction can be limited to the sub-micro and even nanoscale (Huh et al, 2017;Malshe et al, 2010), As an example, with an ultra-short pulse coupled with an atomic force microscope (AFM) cantilever tip (Fig. 16 a and 16b), the dimension of the machined groove can be confined to be less than 100 nm (Han et al, 2022;Lee et al, 2010). The alternative way is to decrease the size of the electrolytic cell, which then acts as both the electrolytic cell and the tool.…”
Section: Tool Designs For Machining Of Sub-micro and Nanostructuresmentioning
confidence: 99%